Berberine: chemical, pharmacological aspects and its potential prophylactic relationship with Alzheimer's disease (Research, Society and Development, 2023)
This article aimed to review the chemical and pharmacological aspects of berberine, correlating them with the pathophysiological outcome of Alzheimer's disease (AD). A descriptive study of the narrative literature review type was carried out. The investigative locus was carried out through an electronic search in the Scientific Electronic Library (SciELO), Latin American and Caribbean Center on Health Sciences Information (BIREME-PAHO-WHO) and National Library of Medicine, USA (PubMed), being Articles published between 2018 and 2023 in English, Portuguese and Spanish were considered. The search for articles was based on the search for the keywords berberine and Alzheimer's disease, using the Boolean operator and to connect these terms. Berberine is classified as a quaternary ammonium salt, it is part of the group of isoquinoline alkaloids called protoberberine. Some studies indicate that berberine is able to attenuate the inflammatory process, excitotoxicity, excessive activity of free radicals and deposition of senile plaques. This review summarized the chemical and physical-chemical aspects of berberine, relating them to bioavailability parameters; clarified some points of the etiology, pathophysiology and clinical manifestations of Alzheimer's disease, considering its complexity; and correlated them considering the main action switches of the neuroprotective substance. In vivo and in vitro studies demonstrate that berberine has therapeutic potential for the treatment of Alzheimer's disease. However, it is still not possible to state whether these results are translational. To verify its effectiveness in humans and estimate possible therapeutic doses, if necessary, robust clinical studies.